ANALISIS PERILAKU ORGANISASI UNTUK MENCAPAI EFEKTIVITAS ORGANISASI PADA JEJARING MASYARAKAT AIR BERSIH DAN SANITASI PASURUAN - jurnalpps pps; Cathrine Sri Hartati; Ruddy Winarko; Dardiri ÔÇì (Jurnal Manajerial Bisnis, 2020)
ABSTRACT The purpose of this study is to determine the description of organizational behavior, strategies to achieve effectiveness in JEMARIS organization. ethod: This research is qualitative research. The method used in this research is interview, observation and document tela'ah. The subject of this research is the board and members of the community network of clean water and sanitation Pasuruan. Data analysis with triangulation of qualitative data obtained from in-depth interview, FGD, Observation, and document review.Research results: organizational behavior in JEMARIS, covering people relationships, Structure, Technology, Environment, Optimization Objectives, System Perspective, Pressure, Accuracy, Target Adaptation, Job Satisfaction, Responsibility. What is inside the JEMARIS organization is very flexible and diverse. Demonstrates that organizational behavior greatly determines the effectiveness of the organization.Conclusion: Organizational behavior in JEMARIS is very diverse, it can be seen there is still a difference in looking at internal organizational issues, organizational strategy is absolutely necessary to achieve organizational effectiveness. Keywords: organizational behavior, organizational effectiveness